Associations of time to return to performance following acute posterior thigh injuries with running biomechanics, hamstring function, and structure in collegiate sprinters: A prospective cohort design. (December 2022) - Otsuka, M.; Isaka, T.; Terada, M.; Arimitsu, T.; Kurihara, T.; Shinohara, Y.
Abstract: Background: The time to return to sport from acute hamstring strain injuries is associated with several functional and structural impairments. However, not all previous studies assessed the preinjury level before acute hamstring strain injuries directly. The purpose of this study was to examine the associations of the time to return to performance following acute hamstring strain injuries with deficits in running biomechanics, hamstring function and structure in collegiate sprinters by a prospective study. Methods: Using a prospective cohort design, 72 participants were recruited from a collegiate track and field team. At the preinjury assessment, a 60-m running-specific test, passive straight leg raise test and isometric knee flexion strength test were assessed at the beginning of the competitive season for three consecutive years (2017–2019). Afterwards, postinjury examinations were performed only in sprinters with acute hamstring strain injuries. Findings: Twelve sprinters strained their hamstring muscle (incidence rate of hamstring strain injuries: 16.7%); the majority ( n  = 10) were classified as grades 0–2. The running speed deficit of the running-specific test was associated with the time to return to performance as well as the passive straight leg raise test deficit. In the running-specific test, lower-limb kinetic deficits were more strongly associated with the time to return to performance compared to lower-limb kinematic deficits. Interpretation: A running-specific test may be considered one of the most convenient and valid tests for assessing rehabilitation progress after acute hamstring strain injuries. Highlights: Incidence rate of hamstring strain injuries was 16.7% during competition season. Majority (83.3%) of injuries was grades 0–2 and the other (16.7%) was grade 3. Running speed and kinetic deficits relate to time to return to performance. Altered hamstring strength and flexibility relate to rehabilitation process. Magnetic resonance image measures may not be related to rehabilitation process.